Strategies For Building The Competitive Advantage of Traditional Balinese Herbal Products - Dewi, Ni Kadek Dian Winda; Yunita, Putu Irma (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to explain the strategies used by traditional Balinese herbal companies to build competitive advantage by exploring how internal resources and capabilities are managed within an increasingly competitive herbal industry. The research was conducted in three Balinese herbal companies CV Nadis Herbal, PT Varash Indonesia Jaya, and CV Padma Medikal Husada using a descriptive qualitative method with a phenomenological approach. Data were gathered through observation, semi-structured interviews, and documentation. The Miles & Huberman interactive analysis model and NVivo 15 software were employed for coding and thematic analysis. The theoretical frameworks applied include the Resource-Based View (RBV), and VRIO. The findings highlight four dominant strategic orientations: human resource strategy, operational strategy, marketing strategy, and financial strategy. Competitive advantage is shaped through innovations rooted in traditional knowledge, consistent product quality, utilization of Bali’s distinctive natural resources, and compliance with BPOM regulations. VRIO analysis indicates that several internal resources are valuable, rare, and difficult to imitate, enabling sustainable competitive advantage. The study concludes that the primary strength of Balinese traditional herbal companies lies in their ability to integrate cultural identity, inherited tacit knowledge, and effective resource management. The synergy of operational, human resource, marketing, and financial strategies substantially enhances their competitive position. The research focuses on only three companies, limiting the generalizability of findings. This study contributes to strategic management scholarship within the traditional herbal industry and offers practical insights for herbal SMEs seeking to strengthen their competitive strategies.